The relationship between fear of competition and stress as perceived by elite athletes - Park, S. H.; Ahn, H. (Research in Dance and Physical Activity, 2024)
The purpose of this study was to verify the relationship between elite athletes` perceived fear of competition and stress related to training and competition. To solve this purpose, relevant data was collected, results were calculated based on data analysis procedures, and discussed based on previous research. The difference in fear of competition according to stress level was found to be statistically significant, and in particular, the group experiencing severe stress was found to feel more fear of competition than the normal stress group. In addition, as a result of conducting a correlation analysis to determine the relationship between stress and fear of competition, stress and fear of competition were shown to be positively correlated, and it was confirmed that as fear of competition increased, stress also increased, and the factors affecting competition fear were identified. As a result of the analysis, it was confirmed that all fear factors had an effect on stress, with an effect of approximately 39%.